Larval description and chaetotaxic analysis of Gyrinus monrosi Mouchamps, 1957 (Coleoptera: Gyrinidae) - Michat, Mariano (2010)
Fil: Michat, Mariano. Facultad de Ciencias Exactas y Naturales. UBA; Argentina